2018
DOI: 10.1002/cssc.201702305
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Decomposition of Crystalline Cellulose in the Presence of Protonated Layered Niobium Molybdate Solid Acid Catalyst

Abstract: Direct depolymerization of crystalline cellulose into water-soluble sugars by solvent-free ball milling was examined in the presence of a strongly acidic layered metal oxide, HNbMoO , resulting in full conversion with 72 % yield of water-soluble sugars. Measurements by C cross-polarization magic angle spinning NMR spectroscopy and X-ray diffraction revealed that amorphization of cellulose occurred rapidly within 10 min. Scanning electron microscopy equipped with an energy dispersive X-ray indicated that the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…More recently, another layered solid, protonated niobium molybdate catalyst (HNbMoO. ), was found to be especially performing in cellulose depolymerization [97].…”
Section: Solvent-free Approaches For Recovery and Elaboration Of Biommentioning
confidence: 99%
“…More recently, another layered solid, protonated niobium molybdate catalyst (HNbMoO. ), was found to be especially performing in cellulose depolymerization [97].…”
Section: Solvent-free Approaches For Recovery and Elaboration Of Biommentioning
confidence: 99%
“…Protonated layered niobium molybdate and tantalum molybdate, HNbMoO 6 and HTaMoO 6 , function as solid acid catalysts, whereas other layered metal oxides such as HTiNbO 5 and HNbWO 6 do not work because reactants cannot enter the interlayers [12][13][14][15][16][17][18][19][20]. The characteristics of layered HNbMoO 6 and HTaMoO 6 as solid acid catalysts are their unique ability of intercalation of reactants within the interlayers with strong Brønsted acid sites and high tolerance against water.…”
Section: Layered Metal Oxidesmentioning
confidence: 99%
“…In other words, cellulose depolymerization over HNbMoO 6 was difficult because cellulose is a big molecule and insoluble in water [13]. In these regards, the mechanochemical reaction as a different methodology was adopted for cellulose depolymerization [20]. It has been reported that ball-milling of crystalline cellulose in the presence of acidic kaolinite, a layered clay mineral could depolymerize it and the solid acidity of additives is important to accelerate the reaction [21].…”
Section: Layered Metal Oxidesmentioning
confidence: 99%
See 2 more Smart Citations